The Impact of Advanced Driver-Assistance Systems (ADAS) on Road Safety in Nigeria - Sule, Samaila Yerima; Bitrus, Emmanuel; Solomon, Yamta (Darul Yasin Al Sys, 2024)
This study investigates the impact of Advanced Driver-Assistance Systems (ADAS) on road safety in Nigeria, focusing on their effectiveness in reducing traffic accidents, public awareness, and the challenges hindering their adoption. Utilizing a descriptive survey research design, data were collected from 310 respondents, including administrators, teachers, and students across various Government Technical Colleges in Adamawa State. The study revealed a strong positive correlation between the availability of ADAS and the reduction of road traffic accidents (r = 0.65, p = 0.002) and a significant association between public awareness of ADAS and safer driving behaviors (r = 0.60, p = 0.003). However, economic and infrastructural challenges were identified as significant barriers to the adoption of these technologies (r = -0.70, p = 0.001). Based on the findings, it is recommended that comprehensive public awareness campaigns be implemented to educate drivers on ADAS benefits, government financial incentives be introduced to encourage the purchase of ADAS-equipped vehicles, investments be made to improve road infrastructure, and research and development initiatives be fostered to create cost-effective ADAS solutions tailored to Nigeria’s driving conditions. Addressing these challenges and implementing these recommendations can lead to enhanced road safety and reduced accident rates, making it essential for stakeholders to collaborate in fostering a safer driving environment.